The Role of Social Capital as a Privilege for Being a Well-educated Woman in Terms of Economic Status - Siti Nur Aisyah (Sciences du Nord Economics and Business, 2025)
A well-educated woman is a part of changes for the civilization of the world and teaching a woman contributes a high revolution. This study elaborates an analysis of the narratives of Indonesian young woman undergoing the supporting system where it is highly related to the parent’s support, social support, social capital support and social network. In terms of economic status of the family, given the role of social factors, this article examines how from a social network, social capital, and social support perspective with a particular focus on underrepresented women in higher education. This article is based on a phenomenological review in which evidence suggests that students' networks including family, ethnic and religious affiliation, friends, and the environment in which they live play a role in decision-making as educated women. The article details and explains how network members from underrepresented groups (women) complement each other in terms of the resources offered and contribute to a woman's life.